2019
DOI: 10.1126/sciadv.aax5489
|View full text |Cite
|
Sign up to set email alerts
|

Why Molière most likely did write his plays

Abstract: Quantitative linguistics contradicts the much publicized theory naming Corneille as the author of Molière’s masterpieces.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Authorship attribution [Juola, 2006,Stamatatos, 2009,Grieve, 2005, Jockers and Witten, 2010, strictly defined, is the task of analyzing a document to determine, not its meaning, but the identity of the person who created it. For example, a recent paper [Cafiero and Camps, 2019] addressed the question of Molière's writings with a large-scale study of various attributes of his work, including lexicon, rhyme, morphology (including a separate study of affixes), morphosyntax, and function words, comparing writings traditionally attributed to Molière with some of his contemporaries. They found that Molière's writings displayed both the internal stylistic consistency as well as the systematic differences from others that would be expected if he had been writing his own work.…”
Section: Authorship Attributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Authorship attribution [Juola, 2006,Stamatatos, 2009,Grieve, 2005, Jockers and Witten, 2010, strictly defined, is the task of analyzing a document to determine, not its meaning, but the identity of the person who created it. For example, a recent paper [Cafiero and Camps, 2019] addressed the question of Molière's writings with a large-scale study of various attributes of his work, including lexicon, rhyme, morphology (including a separate study of affixes), morphosyntax, and function words, comparing writings traditionally attributed to Molière with some of his contemporaries. They found that Molière's writings displayed both the internal stylistic consistency as well as the systematic differences from others that would be expected if he had been writing his own work.…”
Section: Authorship Attributionmentioning
confidence: 99%
“…2006] have proposed using sentence length, vocabulary complexity, vocabulary overlap, synonym pairs, parts of speech, and many others. One of the most powerful and commonly used feature sets are character clusters (formally called N-grams) [Cavnar and Trenkle, 1994, Stamatatos, 2013, Mikros and Perifanos, 2013, Cafiero and Camps, 2019, groups of N adjacent characters without regard to word boundaries-a n-gram can be at the beginning, end, or the middle of a word, or even incorporate the end of one word, a separating space, and the beginning of another. Rudman [Rudman, 1998] has estimated that more than a thousand feature sets have been used successfully in authorship attribution studies.…”
Section: Authorship Attributionmentioning
confidence: 99%
See 3 more Smart Citations